2009
DOI: 10.4319/lo.2009.54.4.1152
|View full text |Cite
|
Sign up to set email alerts
|

UV‐enhanced fish predation and the differential migration of zooplankton to UV radiation and fish

Abstract: The intensity and spectral composition of visible light are known to influence fish predation on zooplankton. However, in clear-water systems, ultraviolet (UV) radiation (UVR) may also influence fish predation, directly through UV-enhanced foraging, indirectly through alterations in predator-prey overlap, or in a combination of the two. Here we test the hypothesis that UVR facilitates fish predation on zooplankton in an oligotrophic lake. Experiments were conducted in 2.2-m-long UV-transparent or UV-blocking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…This is warranted to some extent by the importance of Daphnia in pelagic ecosystems in inland waters (Pace 1984;Carpenter et al 1998;Sarnelle 2005), yet other species are likely to be responsive to different selective pressures. For example, in a series of in situ experimental studies in a lake in Pennsylvania, D. catawba responded more strongly to UV than to fish kairomones, while the reverse was true for L. minutus (Leech et al 2009). Smaller species, such as rotifers, will also tend to be less susceptible to visual predators because of their small size.…”
Section: Caveats and Missing Linksmentioning
confidence: 99%
See 2 more Smart Citations
“…This is warranted to some extent by the importance of Daphnia in pelagic ecosystems in inland waters (Pace 1984;Carpenter et al 1998;Sarnelle 2005), yet other species are likely to be responsive to different selective pressures. For example, in a series of in situ experimental studies in a lake in Pennsylvania, D. catawba responded more strongly to UV than to fish kairomones, while the reverse was true for L. minutus (Leech et al 2009). Smaller species, such as rotifers, will also tend to be less susceptible to visual predators because of their small size.…”
Section: Caveats and Missing Linksmentioning
confidence: 99%
“…In addition, there can also be strong seasonal variation in visual predation pressures due to changes in temperature or production of YOY fish in both marine (Bollens and Frost 1989b;) and freshwater (van Gool and Ringelberg 2002) systems. This is particularly important given that UV may enhance the feeding ability of YOY fish (Leech et al 2009). These seasonal shifts in predation pressure across seasonal transparency gradients may or may not parallel those observed across water bodies of differing transparency.…”
Section: Caveats and Missing Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, we found additive, not interactive, effects of the immediate and developmental lighting environment on predation efficiency in newts. Regardless of developmental group, prey survival was higher in the UV2 testing environment, meaning that, as in fishes [2][3][4], the use of UV cues enhances predation efficiency in newt larvae. We also found that UV-deprived larvae foraged less efficiently than larvae reared with UV light.…”
Section: Discussionmentioning
confidence: 99%
“…When UV cues are not accessible, animals' foraging efficiency is directly negatively affected [2,3]. A recent study demonstrated that, at least in zooplankton predators, UV vision allows location of UV-absorbing food items at greater distances and angles [4].…”
Section: Introductionmentioning
confidence: 99%